2021
DOI: 10.1029/2021jb022026
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Earth's Volatile Delivery With Tin

Abstract: The habitability of Earth depends intrinsically on the presence of volatile elements, and therefore the timing and origin of volatile elements delivery to Earth is a key question, yet to be answered. Volatile elements are depleted in terrestrial planets compared to the Sun's photosphere with degree of depletion generally increasing with decreasing condensation temperature (Palme & O'Neill, 2013). The two most extreme mechanisms that could explain this depletion are (a) a loss of volatile elements by syn-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 129 publications
(276 reference statements)
0
6
0
Order By: Relevance
“…Previous experiments have shown that even at high T conditions there is a significant fractionation of isotopes of elements such as carbon (Satish‐Kumar et al., 2011), nitrogen (Y. Li, Marty, et al., 2016; Shi et al., 2022), silicon (Shahar et al., 2009), and tin (Kubik et al., 2021) associated with core formation. This fractionation occurs due to the influence of mass differences on Gibbs energies in coexisting metal and silicate phases, and scales with ( m h – m l )/( m h ‧ m l ) (Equation S8 in Supporting Information S1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous experiments have shown that even at high T conditions there is a significant fractionation of isotopes of elements such as carbon (Satish‐Kumar et al., 2011), nitrogen (Y. Li, Marty, et al., 2016; Shi et al., 2022), silicon (Shahar et al., 2009), and tin (Kubik et al., 2021) associated with core formation. This fractionation occurs due to the influence of mass differences on Gibbs energies in coexisting metal and silicate phases, and scales with ( m h – m l )/( m h ‧ m l ) (Equation S8 in Supporting Information S1).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, recently Kubik et al found an enrichment of the heavy Sn isotope in Fe−Sn(−S) metallic liquids rather than silicate melts at high T−P conditions, 34 which was likely to indicate other controlling factors of Sn isotope fractionation (e.g., metallic structures or T−P conditions) and need further investigation. relative to NRIXS measurements has also been found in minerals of other Mossbauer-active elements such as Fe and Eu.…”
Section: Controlling Factors Of Sn Isotope Fractionationmentioning
confidence: 99%
“…30−32 The knowledge of equilibrium Sn isotope fractionation factors among minerals is the quantitative basis for understanding the fractionation mechanisms of Sn isotopes and investigating geological and cosmochemical processes using Sn isotopes. Currently, the lack of such knowledge has limited the interpretations of Sn isotope data in nature and experiments (e.g., ref 14,33,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tin is one of the few trace elements that shows secular increase in abundance in glacial deposits through time (Gaschnig et al, 2016) due to its incompatible behaviour. Significant Sn isotope fractionation has been reported in terrestrial samples (Badullovich et al, 2017;Wang et al, 2018) and in a number of geological processes such as liquid-vapour separation (She et al, 2020), redox processes (Roskosz et al, 2020), metal-silicate equilibrium (Kubik et al, 2021), and hydrothermal processes (Liu et al, 2021), indicating that Sn isotopes may be fractionated during continental crust formation. This raises the question of whether there may also be a secular evolution of the Sn isotopic composition in glacial diamictites.…”
Section: Introductionmentioning
confidence: 99%